Analisis Energi Angin Sebagai Pembangkit Energi Listrik di Kecamatan Wawonii Utara - La Ode Sukirman; Irawati; Syamsul Razak Haraty (Jurnal Rekayasa Geofisika Indonesia, 2025)
Research has been carried out to determine the potential for wind energy in North Wawonii dictrict konawe island regency. Research methods include collecting wind speed data and calculating wind energy potential. Wind speed was measured using a Benetech GM816 digital Anemometer from 16 to 21 June 2023 for 9 hours per day, then a wind distribution map was made using Surfer 13 software to determine the distribution of wind direction. The results of the analysis of the average potential wind speed in six days in North Wawonii district range from 2.06 m/s to 5.98 m/s with an average of 3.63 m/s and the resulting power (cp) of 22.34 watts to 33.18 watts with an average of 27.91Watts and Effective Power (Ea) ranges from 11.29 watts to 16.91 watts with an average of 14.22 watts. Based on the results of the analysis of minimum, maximum and average wind speeds in coastal areas and mountainous areas in the North Wawonii area over a period of six days, it can be concluded that the wind speeds that occur have the potential to be utilized because they are classified as class 4 wind speed criteria on the Beaufort scale..